Gd3+-Doped Magnetic Nanoparticles for Biomedical Applications - A. P. Budnyk; T. A. Lastovina; A. L. Bugaev; V. A. Polyakov; K. S. Vetlitsyna-Novikova; M. A. Sirota; K. G. Abdulvakhidov; A. G. Fedorenko; E. O. Podlesnaya; A. V. Soldatov (Journal of Spectroscopy)
Magnetic nanoparticles (MNPs) made of iron oxides with cubic symmetry (Fe3O4, γ-Fe2O3) are demanded objects for multipurpose in biomedical applications as contrast agents for magnetic resonance imaging, magnetically driven carriers for drug delivery, and heaters in hyperthermia cancer treatment. An optimum balance between the right particle size and good magnetic response can be reached by a selection of a synthesis method and by doping with rare earth elements. Here, we present a microwave-assisted polyol synthesis of iron oxide MNPs with actual gadolinium (III) doping from 0.5 to 5.1 mol.%. The resulting MNPs have an average size of 14 nm with narrow size distribution. Their surface was covered by a glycol layer, which prevents aggregation and improves biocompatibility. The magnetic hyperthermia test was performed on 1 and 2 mg/ml aqueous colloidal solutions of MNPs and demonstrated their ability to rise the temperature by 3°C during a 20–30 min run. Therefore, the obtained Gd3+ MNPs are the promising material for biomedicine.